Exploring the perceptions of living donation among potential Moroccan donors in the Netherlands - Charifa Zemouri; Assia Nait Kassi; Muriel Sinselmeijer; Bert Elbertse; Yvonne Mulder; Sara Jobse; Eva-Maria Merz (PLoS ONE, 2025)
Introduction The Moroccan-Dutch population is underrepresented in Dutch donor pools, threatening access to matched blood products and transplants. This study explored Moroccan-Dutch individuals willingness to donate blood, stem cell, and live organ donation, and preferred information dissemination methods. Methods A qualitative and exploratory ethnographic study was employed using a survey followed by a focus group to examine willingness and information needs regarding living donation (blood, stem cells, kidney, liver) among Moroccan-Dutch individuals aged 18–55. Survey results were thematically analysed to inform an interview guide for in-depth focus group. Eight participants (four male, four female) were purposefully invited. The session was recorded, transcribed, and analysed thematically. Results Surveys from 119 persons and one focus group were analysed. Ten themes emerged across tissue types: 1) awareness of need; 2) information and knowledge; 3) donation process; 4) cues to action; 5) attitude; 6) religious legitimacy; 7) health challenges; 8) fear; 9) social cohesion and solidarity; 10) relationship with recipient. Participants were willing to donate blood, but needed reminders to prompt registration. Hesitation around stem cell donation stemmed from unfamiliarity and Islamic uncertainty. For living organ donation, emotional ties to recipients influenced willingness. Most participants were unaware of ethnic matching needs and shortages, and preferred campaigns highlighting these aspects. A multi-component communication strategy was preferred, combining medical, technical, religious, and emotional information, including patient stories, to address gaps and insecurities. Conclusion Participants were unfamiliar with stem cell donation, living organ donation, and ethnic matching. They were willing to donate tissue if aware of the shortage, the need for ethnic matching, and religious legitimacy They sought medical-technical information from donor organisations but preferred religious legitimacy communicated by an Islamic scholar. Participants stressed the need for a tailored campaign addressing barriers, ethnic matching, and reliance on the same community for successful living donation.